Developments in strategic ceramic materials : a collection of papers presented at the 39th International Conference on Advanced Ceramics and Composites, January 25-30, 2015, Daytona Beach, Florida /: a collection of papers presented at the 39th International Conference on Advanced Ceramics and Composites, January 25-30, 2015, Daytona Beach, Florida. (2016) - Unknown
No abstract available